2013
DOI: 10.1039/c3sm50764e
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled surfactant cyclic peptide nanostructures as stabilizing agents

Abstract: A number of cyclic peptides including [FR]4, [FK]4, [WR]4, [CR]4, [AK]4, and [WK]n (n = 3-5) containing L-amino acids were produced using solid-phase peptide synthesis. We hypothesized that an optimal balance of hydrophobicity and charge could generate self-assembled nanostructures in aqueous solution by intramolecular and/or intermolecular interactions. Among all the designed peptides, [WR]n (n = 3-5) generated self-assembled vesicle-like nanostructures at room temperature as shown by transmission electron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 40 publications
(48 reference statements)
1
37
0
Order By: Relevance
“…arginine and L-glycine were synthesized ( Figure 1) using solid phase peptides synthesis. These peptide sequences (Table 1) were selected based on our previous report where cyclic amphipathic peptides were made consisting of hydrophobic (Trp) and positive charge (Arg) residues [34]. Glycine was incorporated in the sequence to add more flexibility in the peptide.…”
Section: Self-assembly Of Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…arginine and L-glycine were synthesized ( Figure 1) using solid phase peptides synthesis. These peptide sequences (Table 1) were selected based on our previous report where cyclic amphipathic peptides were made consisting of hydrophobic (Trp) and positive charge (Arg) residues [34]. Glycine was incorporated in the sequence to add more flexibility in the peptide.…”
Section: Self-assembly Of Peptidesmentioning
confidence: 99%
“…Very recently, tryptophan-and arginine-based cyclic peptides were reported to form self-assembled vesiclelike structures and they have been shown to act as molecular transporters. However, self-assembly process of these peptides was time-consuming (10-12 days) and frequency of nanostructures formation was found to be low [34]. Moreover, they were not explored for macromolecular delivery.…”
Section: Introductionmentioning
confidence: 99%
“…44 Recently, we have performed an extensive investigation on the self-assembly process of a number of cyclic peptides including [FR] 4 , [FK] 4 , [WK] 5 , [CR] 4 , [AK] 4 , and [WR] 4 containing L-amino acids (Figure 14). 45 …”
Section: Peptide Nanostructuresmentioning
confidence: 99%
“…The results indicated that three major elements are involved in the self-assembly process of these cyclic peptides including hydrophobic force, hydrogen bonding by partial β-structures, and/or the Π- Π stacking interactions between tryptophan residues. 45 …”
Section: Peptide Nanostructuresmentioning
confidence: 99%
“…[1][2][3][4][5] An important class of peptides, which may exhibit a wide range of possibilities for biomedical applications is the amphiphilic peptides. [1][2][3][5][6][7][8][9][10][11][12][13] Despite the various characteristics in common with lipids and detergents, such peptides, called surfactant-like peptides (SLPs), present an intrinsic difference that can lead to different physical consequences: the composition and structure of their tail. Unlike conventional surfactants whose hydrophobic tails interact in all directions through hydrophobic interactions, the amphiphilic peptide tail contains not only hydrophobic groups but also hydrophilic sites.…”
Section: Introductionmentioning
confidence: 99%